Step
*
2
of Lemma
sqeq-copath2
1. b : Base
2. a : Base
3. m : Base
4. n : Base
5. is-exception(if n + 1=m then a else b)
⊢ if n + 1=m then a else b ≤ if n=m - 1 then a else b
BY
{ (ExceptionCases (-1) THEN Try (ExceptionSqequal (-1))) }
1
1. b : Base
2. a : Base
3. m : Base
4. n : Base
5. is-exception(if n + 1=m then a else b)
6. n + 1 ∈ ℤ
7. m ∈ ℤ
⊢ if n + 1=m then a else b ≤ if n=m - 1 then a else b
2
1. b : Base
2. a : Base
3. m : Base
4. n : Base
5. is-exception(if n + 1=m then a else b)
6. n + 1 ∈ ℤ
7. is-exception(m)
8. u : Base
9. v : Base
10. m ~ exception(u; v)
⊢ if n + 1=m then a else b ≤ if n=m - 1 then a else b
3
1. b : Base
2. a : Base
3. m : Base
4. n : Base
5. is-exception(if n + 1=m then a else b)
6. is-exception(n + 1)
7. u : Base
8. v : Base
9. n + 1 ~ exception(u; v)
⊢ if n + 1=m then a else b ≤ if n=m - 1 then a else b
Latex:
Latex:
1.  b  :  Base
2.  a  :  Base
3.  m  :  Base
4.  n  :  Base
5.  is-exception(if  n  +  1=m  then  a  else  b)
\mvdash{}  if  n  +  1=m  then  a  else  b  \mleq{}  if  n=m  -  1  then  a  else  b
By
Latex:
(ExceptionCases  (-1)  THEN  Try  (ExceptionSqequal  (-1)))
Home
Index